Limited parasite acquisition by non-native Lepomis gibbosus (Actinopterygii: Centrarchidae) at two ponds in the Upper Rhine basin, Germany - Ondračková, M; Kvach, Y; Martens, A; Jurajda, P (Journal of helminthology, 2019)
Metazoan parasite communities of Lepomis gibbosus (Centrarchidae), one of the most successfully introduced fish species in Europe, were studied at two isolated ponds (Knielingen, Tropfen) along the Upper Rhine in Germany. Nine parasite taxa were observed, including North American species co-introduced to Europe (ancyrocephalid monogeneans, diplostomid trematodes), circumpolar species infecting L. gibbosus in both their native and non-native ranges (bothriocephalid cestodes) and locally acquired parasitic nematodes. Both parasite communities consisted predominantly of North American species. Acquisition of local parasites was not observed at Tropfen, where the fish community comprised just two species, with L. gibbosus dominant. Low prevalence and abundance of acquired parasites was found at Knielingen, which supported a diverse fish community. At Tropfen, a high abundance of the North American parasite Posthodiplostomum centrarchi probably contributed to the lower condition index, hepatomegaly and splenomegaly observed. Due to low local parasite competency, L. gibbosus appears to have no significant impact on parasite dynamics in affected habitats.
Keywords: rybníky; nemoci ryb; splenomegalie; Cestode Infections; Fish Diseases; Ecosystem; prevalence; Trematoda; Trematode Infections; infekce červy třídy Trematoda; Parasites; zvířata; Germany; Splenomegaly; hepatomegalie; Hepatomegaly; Německo; Ponds; cestodózy; Prevalence; Animals; Perciformes; paraziti; ekosystém